Research on Innovative Ways to Integrate "Curriculum Ideological and Political Education" into Higher Vocational English Education (Journal of Global Humanities and Social Sciences, 2024)
In the educational context of the new era, the development of English education in higher vocational colleges has received increasing attention. Integrating it with "curriculum ideological and political education" has become an inevitable trend in cultivating the all-round development of high-quality talents. The integration of higher vocational English into "ideological and political courses" is not only a need to meet the needs of the times but also an important way to improve students' ideological and political literacy and comprehensive English ability. Based on this, this article first analyzes the significance and existing problems of integrating higher vocational English into "curriculum ideological and political education", and then elaborates on specific implementation measures, aiming to provide new ideas and strategies for the development of higher vocational English education.